Digital encyclopedia of Semarangan dance style: Strategies for improving Critical thinking skills in local culture - Nurharini, Atip; Ratnaningrum, Ika (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2026)
Semarangan style dance as an identity of Semarang City is essential to be introduced in order to preserve local culture through innovative teaching materials. This study aims to explore the characteristics of Semarangan style dance, identify strategies for enhancing students’ critical thinking skills related to local culture through digital encyclopedias, and examine the improvement of students’ critical thinking abilities. The research employs a qualitative descriptive phenomenological approach involving 30 elementary school students and teachers in Semarang City. Data were collected through observation, interviews, focus group discussions, and document analysis, and analyzed using interactive analysis techniques. The findings indicate that Semarangan style dance embodies geographical conditions, socio-cultural values, and the multi-ethnic character of Semarang society. Strategies to enhance critical thinking are implemented through stages of dance appreciation, practice, analysis, and evaluation. In conclusion, the use of digital encyclopedias is effective in improving students’ critical thinking skills in cognitive, kinesthetic, and character dimensions. The implications of this study suggest that Semarangan style dance-based digital learning media can serve as an effective model for integrating local cultural content into elementary education, supporting culturally responsive pedagogy and character education. Furthermore, this research provides a pedagogical framework for educators to utilize digital encyclopedias as innovative tools to foster critical thinking while strengthening students’ cultural identity. At a broader level, the findings contribute to efforts in local cultural conservation by positioning traditional dance as a dynamic learning resource within contemporary digital education contexts.